Business complexity and risk management: Evidence from operational risk events in U.S. bank holding companies - Anna Chernobai; Ali K. Ozdagli; Jianlin Wang (Federal Reserve Bank of Boston, 2016)
How does business complexity affect risk management in financial institutions? The commonly used risk measures rely on either balance-sheet or market-based information, both of which may suffer from identification problems when it comes to answering this question. Balance-sheet measures, such as return on assets, capture the risk when it is realized, while empirical identification requires knowledge of the risk when it is actually taken. Market-based measures, such as bond yields, not only ignore the problem that investors are not fully aware of all the risks taken by management due to asymmetric information, but are also contaminated by other confounding factors such as implicit government guarantees associated with the systemic importance of complex financial institutions. To circumvent these problems, we use operational risk events as a risk management measure because (i) the timing of the origin of each event is well identified, and (ii) the risk events can serve as a direct measure of materialized failures in risk management without being influenced by the confounding factors that drive asset prices. Using the gradual deregulation of banks' nonbank activities during 1996-1999 as a natural experiment, we show that t he f requency and magnitude o f o perational r isk e vents i n U .S. b ank h olding c ompanies h ave i ncreased significantly with their business complexity. This trend is particularly strong for banks that were bound by regulations beforehand, especially for those with an existing Section 20 subsidiary, and weaker for other banks that were not bound and for nonbank financial institutions that were not subject to the same regulations to begin with. These results reveal the darker side of post-deregulation diversification, which in earlier studies has been shown to lead to improved stock and earnings performance. Our findings have important implications for the regulation of financial institutions deemed systemically important, a designation tied closely to their complexity by the Bank for International Settlements and the Federal Reserve.
Keywords: G18; G20; G21; G32; L25; 330; operational risk; bank holding companies; financial deregulation; Glass-Steagall Act; business complexity